Adverse childhood experiences and reproductive strategies in a contemporary U.S. population. Issue 1 (11th November 2019) - Holdsworth, Elizabeth A.; Appleton, Allison A.
Abstract: Objectives: Stressful experiences may initiate developmentally plastic responses toward a faster reproductive strategy. This study tests whether adverse childhood experiences (ACEs) are associated with characteristics of faster reproductive strategies: earlier menarche and reduced prenatal investment in offspring in a well‐nourished, low‐immune system burden population. Materials and Methods: We analyzed the first 214 enrollees of the prenatal‐birth Albany Infant and Mother Study. Mother's menarcheal age, offspring gestational age at birth, and cephalization index (head circumference/weight, cm/g) were derived from medical records. Linear regression models tested the contribution of self‐reported ACEs from 0 to 18 years of age to menarcheal age and the contribution of menarcheal age to offspring gestational age and cephalization index. Birth outcome models included covariates self‐reported maternal race, education, prenatal smoking, prenatal diet, newborn sex, parity, delivery method, and labor induction derived from medical records. Results: More ACEs were associated with earlier age at menarche, controlling for covariates ( β = −.18, SE = 0.048, p  < .001), though timing of ACEs relative to menarche is unknown. Earlier menarcheal age was associated with offspring higher cephalization index ( β = −.01, SE = 0.006, p  < .05). Stratified models showed a significant relationship in high (≥2) ACEs group ( β = −.02, SE = 0.009, p  < .05), not present among low ACEs. Menarcheal age predicted gestational age only among those with high ACEs ( β = .22, SE = 0.091, p  < .05). Discussion: In a well‐nourished population, early life stress can result in faster reproductive strategies, initiating sexual maturation earlier, and reducing prenatal investment in individual offspring. Early age at menarche following childhood stress has a stronger relationship with adverse birth outcomes than early menarche without exposure to adverse childhood stress.